Comparison and evaluation of modelling indicators - Yagmur, Sensin Aydin; Ozturk, Leyla Dokuzer (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
Modelling describes the balance between diffuse and directed light. The conditions for perception of objects features like form and texture and human faces clearly and pleasingly are examined under the heading 'modelling' in the literature. In this study, modelling indicators, which have defined metric limits, recommended by several researchers are investigated. The examination results in terms of modelling indicators obtained via a lighting program are compared with each other in the first stage. In the second stage, the examination results are compared with the visual impressions of subjects about a person's face in a mock-up room in Yildiz Technical University, designed as an office for two users within the context of a research project (Project no: 2011-03-01-DOP01). In conclusion, modelling indicators for different lighting scenarios were found not to be coherent with each other and the subjects' impressions.
Keywords: Modelling; modelling indicators; vectoral illuminance; spherical illuminance; Engineering